Sulpicia y su visión lírica. - Argüello Scriba, Sol (2012)
The analysis of the I poem of Sulpicia, the young roman female poet of the I b.C., in latin language, gives us a world of the self liric of the woman who experiments life and love, and also gives us a sight full of passion and freshness, proper of her time, but full of eternity.